Financial Sustainability of Communities in the Context of Ensuring Their Inclusive Development - Lobodina, Zoriana; Trush, Volodymyr (Herald of Economics, 2025)
Introduction. The effectiveness of providing public services to the population depends on the level of financial stability of communities, which is formed under the influence of economic, political and security factors. In the context of military challenges, there is a growing need to improve the management of local financial resources, develop modern methods for assessing financial sustainability, and find tools that can ensure inclusive community development. Purpose. The article is aimed at deepening the theoretical and methodological foundations and developing recommendations for improving the diagnosis of the financial sustainability of communities in the context of ensuring their inclusive development. Methods. The article uses methods of analysis and synthesis, expert assessments, main components, cluster and comparative analysis, and graphical methods. Results. Financial sustainability is defined as an integral indicator of community resilience, reflecting their ability to adapt and recover under the influence of transformational challenges, ensuring the continuous provision of public services and creating conditions for inclusive development. The analysis of existing approaches to its assessment has shown the absence of a unified methodology, which complicates comparative diagnostics and the development of effective management decisions. A system of indicators for the diagnostics of the financial sustainability of communities and opportunities to ensure their inclusive development. Based on the use of the cluster analysis method, four groups of communities have been identified in terms of the level of financial stability and opportunities to ensure inclusive development, from financially viable and investment-active to critically vulnerable, dependent on interbudgetary transfers, and characterized by a low level of implementation of innovative budgeting practices. The identified differences are the information basis for the formation of targeted regional policy, strengthening the financial autonomy of communities, and developing strategies to reduce the risks of financial instability. Discussion. Prospects for further research are seen in the development of a methodology for integral assessment of the financial stability of communities in the context of ensuring their inclusive development.